Estudo do efeito da substituição de átomos de hidrogênios e flúor em propriedades covalentes e iônicas em algumas N,N-nitrosodimetilamina e N,Nnitrosodietilamina - Andrade, Railton Barbosa de (2012)
Nitrosamines are chemicals that have received much attention because of the potential cancer hazard. Studies on the interaction of nitrosamines with the formula RIRIINNO where, RI and RII can be methyl or ethyl groups, with the characterization of direct interaction of nitrosamines with Cytochrome P450 through the cation with the heme iron, demonstrated a metal-ligand interaction through oxygen. Our motivation was to investigate the variation of some ionic and covalent characteristics in the molecules by the replacement of hydrogen atoms by fluorine atoms, because of the existence of the ionic character and also of the covalent character in the interaction (Metal-Ligand). We divided the structures into two groups: N, N-nitrosodimethylamine, N, N-nitrosodiethylamine (a) and N, Nnitrosodiethylamine (b). We performed Optimization and Frequency calculations of 120 structures using Gaussian09 with the methods: DFT/B3LYP (cc-pVTZ) and MP2 (cc-pVTZ) with calculations of charge NBO. Single-point (cc-pVTZ) calculations were performed to analyze the energies and location of some orbitals, to observe the change of the contribution of oxygen in the formation of these orbitals. The results showed a range of values for dipole moment between 0,2566 5,9028 Debye. This variation is directly linked to the dipolar resonance structure. Some substitutions affect the amount of dipole moment and geometry, modifying the structures point group of some. The polarizability has changed very little, because with the addition of fluorine atoms, electrons are more attracted by the atomic nuclei of nitrosamines. We found a correlation between NBO charges of nitrogen atoms (Amino group) with the N-N bond distances. The same correlation was found between the NBO charges on oxygen and the bond distance N=O. We found that the energy of orbital increases when the amount of Fluorine atoms increases. Regarding the location of orbitals in the oxygen, π ligand N=O orbital has little contribution from oxygen.